1996
DOI: 10.1002/art.1780390620
|View full text |Cite
|
Sign up to set email alerts
|

N‐[4‐hydroxyphenyl] retinamide in rheumatoid arthritis: A pilot study

Abstract: Objective. To evaluate the efficacy and tolerability of N‐[4 hydroxyphenyl] retinamide (4‐HPR), a synthetic retinoid, in the treatment of rheumatoid arthritis (RA). Methods. An uncontrolled, open clinical trial with synovial biopsy pre‐ and postmedication to evaluate the clinical effects of 4‐HPR as well as its effects on metalloproteinase gene expression. Results. Twelve patients with severe, longstanding RA were enrolled in this study. Six patients withdrew before study completion, 2 because of drug toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Acitretin, etretinate and Am-80 are reported to be effective in the suppression of experimented multiple serositis [19,20] and psoriasis [4,[21][22][23][24]. In addition, N-[4-hydroxyphenyl] retinoid, and 13-cis retinoic acid are effective in the treatment of experimental rheumatoid arthritis [25]. In our previous studies, Am-80 showed a potent inhibition for the development of CIA in mice by interfering with the production of IL-6 [20].…”
Section: Discussionmentioning
confidence: 99%
“…Acitretin, etretinate and Am-80 are reported to be effective in the suppression of experimented multiple serositis [19,20] and psoriasis [4,[21][22][23][24]. In addition, N-[4-hydroxyphenyl] retinoid, and 13-cis retinoic acid are effective in the treatment of experimental rheumatoid arthritis [25]. In our previous studies, Am-80 showed a potent inhibition for the development of CIA in mice by interfering with the production of IL-6 [20].…”
Section: Discussionmentioning
confidence: 99%
“…Approaches in vitro and in animal models thus far have included exogenous administration of tissue inhibitor of metalloproteinases (TIMP) (113), agents that can increase local production of TIMP such as retinoids (114), and synthetic peptides that inhibit MMPs (115,116). A small pilot study evaluating a synthetic analog of vitamin A as a treatment for RA did not reveal significant clinical improvement (117). Antibiotics such as tetracycline and related compounds, which are inhibitors of MMPs (118)(119)(120), have been shown to be superior to placebo in controlled trials in RA patients.…”
Section: Other Potential Biologic Agentsmentioning
confidence: 99%